Decarbonizing Hospitality: A Theoretical Framework for Achieving Net Zero - Tee, Mooi Kwong Anthony (Centre For Tourism Planning and Development, 2025)
The compelling objective is to introduces a comprehensive theoretical framework for the Malaysian hospitality industry to achieve Net Zero status by addressing significant environmental challenges through sustainable practices. The methodology involved an extensive review of literature, policies, and sustainability initiatives, drawing on data from academic publications, government reports, industry documents, and reputable online sources. Anchored firmly in the ideals of sustainable development, systems thinking, and corporate responsibility, the framework confronts pressing challenges with a suite of strategic initiatives: from achieving Net-Zero ambitions and implementing robust policies to enhancing energy efficiency, managing waste, conserving water, and adopting sustainable procurement practices. It advocates green building standards, fosters innovation and training, and promotes active stakeholder engagement, all while embracing the circular economy and transparency. Financial incentives serve as catalysts, guiding industries toward sustainable practices; key to shrinking carbon footprints, bolstering competitiveness, and contributing meaningfully to global climate efforts. In harmony with Malaysia’s climate ambitions, this approach promises tangible benefits: cost reductions, operational improvements, and a strengthened brand reputation. The call to action is urgent, climate change demands immediate response, highlighting the profound positive ripple effects such efforts can generate for both industry and environment alike. The proposed theoretical framework is designed to guide the industry systematically toward achieving Net Zero status.